Multiannual hydrological responses in Scots pine radial growth within raised bogs in southern Sweden - Edvardsson, Johannes; Hansson, Anton (Silva fennica (Helsinki, Finland : 1967), 2015)
To explore interactions between climate and peatland hydrology, Scots pine ( L.) growing at four raised bogs in southern Sweden were subject to a dendroclimatological study. Radial tree growth reflecting climate and water table fluctuations over multiannual periods was detected as significant negative correlations between tree-ring width (TRW) chronologies and the preceding one to four years total precipitation or river discharge. Systematically stronger negative correlations were obtained when river discharge instead of precipitation was compared to radial tree growth. This indicates that river discharge reflect moisture variability of peat bogs better than what precipitation data does. Meanwhile, monthly precipitation and radial tree growth did not show any clear correlation, whereas spring and early summer temperatures had a positive influence on the tree growth. Our study shows that growth variability of bog pines in the Boreal zone reflect hydrological responses related to a synthesis of climate controlled moisture variability over several year periods. Pinus sylvestris